The chopstick auction: a study of the exposure problem in multi-unit auctions - Florian Englmaier; Pablo Guillén; Loreto Llorente; Sander Onderstal; Rupert Sausgruber (Center for Economic Studies and ifo Institute (CESifo), 2006)
Multi-unit auctions are sometimes plagued by the so-called exposure problem. In this paper, we analyze a simple game called the chopstick auction' in which bidders are confronted with the exposure problem. We do so both in theory and in a laboratory experiment. In theory, the chopstick auction has an efficient equilibrium and is revenue equivalent with the second-price sealed-bid auction in which the exposure problem is not present. In the experiment, however, we find that the chopstick auction is less efficient than the second-price sealed-bid auction and that it yields more [the same] revenue if bidders are inexperienced [experienced].
Keywords: C9; D44; 330